2016
DOI: 10.1111/aas.12717
|View full text |Cite
|
Sign up to set email alerts
|

Post-anaesthetic emergence delirium in adults: incidence, predictors and consequences

Abstract: Male sex, volatile anaesthetics and ETT were factors significantly related to ED. Whether gender, choice of respiratory devices and anaesthetics are true predictors or derived factors of surgery procedures, duration of surgery and the patients' physical condition need further investigation. The most notable clinical consequence of ED was the need of additional staff in order to restrain the agitated patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
3
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(156 citation statements)
references
References 9 publications
4
140
3
9
Order By: Relevance
“…The fi rst assessment of postoperative (also referred to as interval) delirium was done around 24 h after surgery; 20 we selected the timing of the fi rst assessment to avoid diagnosing emergence delirium that can occur immediately after general anaesthesia and is not associated with adverse outcomes. 21,22 Twice daily (in the morning from 0800 h to 1000 h and in the evening from 1800 h to 2000 h) until the seventh day after surgery, we assessed delirium by the Confusion Assessment Method for the ICU (CAM-ICU); (appendix), 23 which has been validated in Chinese patients in the ICU setting 24 and the feasibility of which had been established in our other studies. 25,26 CAM-ICU addresses the four features of delirium, namely, acute onset of mental status changes or a fl uctuating course, inattention, disorganised thinking, and altered level of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…The fi rst assessment of postoperative (also referred to as interval) delirium was done around 24 h after surgery; 20 we selected the timing of the fi rst assessment to avoid diagnosing emergence delirium that can occur immediately after general anaesthesia and is not associated with adverse outcomes. 21,22 Twice daily (in the morning from 0800 h to 1000 h and in the evening from 1800 h to 2000 h) until the seventh day after surgery, we assessed delirium by the Confusion Assessment Method for the ICU (CAM-ICU); (appendix), 23 which has been validated in Chinese patients in the ICU setting 24 and the feasibility of which had been established in our other studies. 25,26 CAM-ICU addresses the four features of delirium, namely, acute onset of mental status changes or a fl uctuating course, inattention, disorganised thinking, and altered level of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Lepouse found that probable Volume 8 Issue 4 -2017 etiologies of emergence delirium most often included existence of tracheal tube, pain, and anxiety [2]. Another study reported male sex, volatile anaesthetics and endotracheal tube were the factors significantly related to ED [4]. In awake patient, tracheal tube can be stressing, and therefore should be removed as early as possible [2,5].…”
Section: Discussionmentioning
confidence: 99%
“…Self-extubation and removal of catheters can lead to aspiration pneumonia or emergency surgery [2]. The most notable clinical consequence was the need of additional staff to restrain the agitated patient [4]. Postoperative agitation can be reduced by providing continuous analgesia, and by removing the tracheal tube and urinary catheter as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…69 As escalas de agitação-sedação, como a Escala de Agitação-Sedação de Richmond (RASS -Richmond Agitation-Sedation Scale) ou a Escala de Agitação-Sedação de Riker, foram utilizadas para avaliar a emergência após a anestesia em algumas pesquisas importantes. [70][71][72][73][74] Esses estudos analisaram a condição mental do paciente logo após a anestesia e encontraram associação entre o tempo de permanência na SRPA e eventos adversos pós-operatórios. Essas escalas devem ser utilizadas juntamente com uma ferramenta de avaliação do delirium.…”
Section: Essa Escala é Baseada Nos Critérios Do Diagnostic and Statisunclassified